Antinociceptive Effect of Liposomal Bupivacaine Formulations After Intrathecal Administration in Rats - YİĞİT, İlker (Turk J Med Sci, 2019)
BACKGROUND/AIM: Based on our previous in vitro study with multilamellar liposomal bupivacaine (MLB) versus bupivacaine alone in artificial cerebrospinal fluid, we aimed to investigate in vivo antinociceptive effect of intrathecal MLB by determining tail flick latency (TFL) time after thermal stimulation in rats. MATERIALS AND METHODS: After preparing MLB and high-yield drug entrapment in liposome (HYDEL) bupivacaine, 18 female Wistar rats were assigned to 3 groups as control (bupivacaine) and study groups (MLB and HYDEL bupivacaine) including 6 rats in each group to administer these drugs intrathecally. Antinociceptive activity was determined in terms of TFL time after thermal stimulation. Maximum possible effect (MPE) calculated from TFL times and rats with motor block were documented. RESULTS: TFL times after intrathecal injection of HYDEL bupivacaine were significantly longer than that of the control and MLB groups (P < 0.05) and returned to baseline 180 min after intrathecal injection. MPE (100%) with intrathecal HYDEL bupivacaine occurred between 10 to 45 min. Afterwards, MPEs were 70% and 50% for the control and MLB groups, respectively. Motor block disappeared after 20 min in the study groups while it lasted 75 min in the control. CONCLUSION: Intrathecal administration of MLB and HYDEL bupivacaine in rats resulted in longer duration of antinociceptive activity with shorter motor block duration.